New television, globalisation, and the East Asian cultural imagination - Keane, Michael, 1952- (Hong Kong University Press, 2007)
This volume is divided into three parts: 'Adaptation and Local Production in East Asia', 'Formats, Clones, and Generic Variations' and 'New Television'.